Representasi Makna Denotasi dan Konotasi dalam Lirik Lagu Kun Fayakun (Analisis Semiotika Roland Barthes) - Trimo Wati, Trimo Wati; Dina Safira Ikmaliani; Mustolehudin (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to describe the meaning implied in the Arabic song “Kun Fayakun” lyrics through translation and study process analysis. As for this research, the author used the qualitative-descriptive method by making observations through existing data, looking for patterns between relationships with various concepts that have not been previously determined, analyzing, then providing understanding and explanations. The data were collected by observation and documentation technique and analyzed by Roland Barthes's semiotic theory. The outcome that was gained from this research is as follows: 12 the denotative and 12 connotative meaning which have an important role in helping the reader to understand the song lyrics of literary meaning and its implicit meaning.